Could Hallucinogens Induce Permanent Pupillary Changes in (Ab)users? A Case Report from New Zealand - Ahmed Al-Imam (Case Reports in Neurological Medicine)
An eighteen-year-old female patient of the Caucasian ethnicity from Australasia presented with a persistently dilated pupil causing her discomfort and occasional burning sensation when she is outdoors due to oversensitivity to sunlight. However, her pupillary reaction to light (pupillary light reflex) was intact. The patient is a known user of psychedelic substances (entheogens) including LSD, NBOMe, psilocybin, and DMT. The condition affects both eyes to the same extent. Thorough medical, neurological, and radiological examinations, including an EEG and an MRI of the head and neck region, were completely normal. All these tests failed to detect any pathophysiological or anatomical abnormalities. The patient is a known case of chronic endogenous depression in association with attention deficit hyperactivity disorder, for which she is taking citalopram and Ritalin, respectively. There was neither a family history nor a similar congenital condition in her family.